The Missing Link Between Financial Constraints and Productivity - Marialuz Moreno Badia; Veerle Slootmaekers (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2008)
This paper provides new evidence on the link between finance and firm-level productivity focusing on the case of Estonia. We contribute to the literature in two important respects: (1) we look explicitly at the role of financial constraints; and (2) we develop a methodology that corrects for the misspecification problems of previous studies. Our results indicate that young and highly indebted firms tend to be more financially constrained. Overall, a large number of firms shows some degree of financial constraints, with firms in the primary sector being the most constrained. More importantly, we find that financial constraints do not lower productivity for most sectors with the exception of R&D, where the dampening effect of financial constraints on productivity is remarkably large. These results are robust to a variety of sensitivity tests.
Keywords: D24; G32; O16; P27; 330; financing constraints; productivity; SMEs; Verschuldungsrestriktion; Forschungsfinanzierung; Produktivität; KMU; Estland